COVID-19 Impact on Medical Practice in Sub-Saharan Africa; The Need to Guard Against Medical Negligence: A Case Report in a Health Care Facility in Kumasi, Ghana - Paul Poku Sampene Ossei; William Gilbert Ayibor; John Taylor; Lawrence Agyemang; Kwabena Owusu Aninkora; Bright Opoku Asante (SAGE Publishing, 2021)
With the novel coronavirus disease 2019 (COVID-19) still in pandemic mode, according to the World Health Organization (WHO), the African continent has experienced continued growth in the total tally. According to the Africa Centers for Disease Control and Prevention (CDC), the virus has spread to almost all 54 recognized African countries. Figures from the CDC indicate that the highly affected countries include South Africa, Egypt, Nigeria, Algeria, Morocco, and Ghana (with more than 55 000 cases and 400 deaths as of the time of writing). The WHO and the United Nations have projected the ongoing pandemic could push medical practitioners toward high rates of clinical misdiagnosis. So far, the coronavirus pandemic has been more devastating and life-threatening than the usual seasonal flu. As of the time of writing, here is presently no proven vaccine or treatment for the disease, with the vaccines still under development; hence, a timely and accurate diagnosis could prove critical. Patients can also receive supportive care earlier if they are diagnosed early. Considering the fact that the coronavirus infection mimics the signs and symptoms of normal flu and other respiratory infections, a problem now emerges, where these symptoms are treated as manifestations of the deadly virus. This has caused a diagnostic dilemma in the absence of laboratory tests with new cases adding to the pool daily. In Ghana, many patients on suspicion of flu-like symptoms are sometimes denied the care so deserved due to the stigma associated with the disease, often in cases where laboratory tests are absent. This study is a postmortem report of a client who died while on admission at a private medical facility. It was an unconfirmed case of COVID-19, and the client was left unattended to and died, having spent 8 days on the ward. His test report was not done initially, but the diagnosis was purely based on suspicion. Nasopharyngeal swabs conducted on the fifth day of admission proved negative. Results became available on the day of the client's demise. Postmortem findings established the actual cause of death, and it was not COVID-19 related.